SOIL INDICATORS IN SUSTAINABLE AGRICULLTURE PRODUCTION - Gajić, Boško; Sredojević, Zorica; Dugalić, Goran (Economics of Agriculture, 2006)
The purpose of this paper is to present and discuss soil physical, chemical and biological indicators at the national level, as well as the progres made in their use for sustainable development assessment. The population pressure adds to the need protect the existing soil resources. There is therefore a need for developing soil indikators in order to measure the sustainability of land use and management for different human activities. Efforts are made towards a better understanding of the factors that may affect the soil resource, and these factors are then translated into indicators. Only an integrated approach combining several relevant indicators can give answers to the complex questions of soil quality and sustainable soil use.